2012
DOI: 10.1007/s00595-012-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

Hand-assisted laparoscopic splenectomy for thrombocytopenia in patients with cirrhosis

Abstract: HALS splenectomy was a very feasible and appropriate procedure for cirrhotic patients with hypersplenism. PSVT was a frequent complication and large splenic vein diameter, high serum bilirubin, and high ICG R-15 were found to be significant risk factors for PSVT after HALS splenectomy in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 23 publications
0
38
1
Order By: Relevance
“…7,12,13 We also reported in a series of HALS for 28 patients with cirrhosis and thrombocytopenia that operation time, estimated blood loss, postoperative complications, and duration of hospital stay were similar to those reported previously, although simultaneous hepatectomy and esophagogastric devascularization were performed in 7 and 5 patients, respectively. 14 PVT is an important and potentially lifethreatening complication associated with splenectomy that has been reported to occur in 8-10% of patients. [15][16][17] In the current study, PVT occurred in 8 cases (18%), which was slightly greater than the previously reported rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12,13 We also reported in a series of HALS for 28 patients with cirrhosis and thrombocytopenia that operation time, estimated blood loss, postoperative complications, and duration of hospital stay were similar to those reported previously, although simultaneous hepatectomy and esophagogastric devascularization were performed in 7 and 5 patients, respectively. 14 PVT is an important and potentially lifethreatening complication associated with splenectomy that has been reported to occur in 8-10% of patients. [15][16][17] In the current study, PVT occurred in 8 cases (18%), which was slightly greater than the previously reported rates.…”
Section: Discussionmentioning
confidence: 99%
“…14 In this study, we aimed to assess the short-term results of LS and its influence on hypersplenism and long-term liver function in the patients with chronic liver disease.…”
mentioning
confidence: 99%
“…After exclusion, 8 papers were included in our meta-analysis (Figure 1) [17–24]. Notably, a randomized controlled trial by Wang et al was terminated due to the absence of funding support [23].…”
Section: Resultsmentioning
confidence: 99%
“…One study found a significant correlation between thrombocytopenia and aetiology of cirrhosis. 20 In addition, another study showed that platelet distribution returned to normal after splenectomy, 21 which likely eliminated platelet retention by the splenic blood pool and removed the site of hypersplenism. However, peripheral cytopenia in hepatitis B-related cirrhotic portal hypertension are thought to be caused by several factors.…”
Section: Discussionmentioning
confidence: 99%